Rdzogs pa chen po sñiṅ thig gi khrid yig go bde bklags chog tu bkod pa lhun grub rtogs paʼi raṅ sgra Kun bzaṅ thugs mdzod gu yaṅs sñiṅ gi thig le : an introduction to the practice of the Kloṅ chen sñiṅ thig system of Rdzogs-chen - Blo-bde (Sherab Gyaltsen Lama, 1976)
An introduction to meditational practice according to the teachings of the Kloṅ chen sñiṅ thig visions of 'Jigs-med-gliṅ-pa, 1729 or 30-1798.